The results of radiation-hygienic monitoring of milk and potatoes producedin local farms in radioactive contaminated zones - Nikolaenko, Elena; Popova, Ekaterina N. (Journal of the Belarusian State University. Ecology, 2026)
The estimation of 137Cs and 90Sr specific activity levels in food personal households that the most consumed of rural belorusian population (milk and potatoes) on the radioactive contamination zones of the Gomel, Mogilev, Brest regions of the Republic of Belarus in 2013–2025 have been done. The radiation-hygienic monitoring in personal household results of state sanitary supervision data have been used for analysis in the article. The reference levels of 137Cs and 90Sr in food were exceed only in 2013–2022 in few samples of potatoes and milk from some settlements (1–10 settlements annually) only in the Bragin, Dobrush, Chechersk, Khoiniki and Narovlya districts of Gomel region and Belynichi and Krasnopolye districts of Mogilev region. Since 2023 the reference levels of 137Cs and 90Sr in milk and potatoes were not exceed but in some samples of vegetables and berries in the Gomel region the excesses of reference levels have been registered in 28 samples: 137Cs – in 2 samples of greens and 2 samples of strawberries from 2 settlements; 90Sr – in 24 samples of carrots and beets from 10 settlements. The number of settlements and samples in which the 137Cs and 90Sr reference levels were exceed and specific activity of 137Cs and 90Sr in milk and potatoes (average, maximum, 75th percentile) from personal household in 2018–2022 heave been assessed. The 75th percentile of the 137Cs specific activity in the most regions of the Republic of Belarus were: milk – up to 15 Bq/kg, potatoes – up to 20 Bq/kg, as well as 90Sr: milk – up to 2 Bq/kg, potatoes – up to 1.5 Bq/kg. On the modern stage after the Chernobyl accident the radiological situation for last 10 years is stable, dynamic of the average specific activity of 137Cs and 90Sr levels in local food were unchanging, the current reference levels of 137Cs and 90Sr specific activity in milk were exceed only in some cases which does not depend on the radioactive contamination density of the settlements and depend on the peculiarities of personal household management and the geochemical characteristics of the soils.